What Is to be Done, and What Will I Do? : Confronting the Biggest Challenges of Our Time - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group, addressed the theme of what is to be done, and what will I do? He opened with stories from his life, which made him realize that activism could drive social change. World Bank Group has set goals to end extreme poverty by 2030 and to boost shared prosperity for the bottom 40 percent in every developing country. These goals will drive our work going forward. But three major challenges will determine whether we succeed: achieving inclusive economic growth; investing in people; and slowing the rising tide of climate change. Finally he concludes saying that, whatever you do, please remember that the time is now for all of us to work together to bend the arc of history toward justice.